Analyzing Indonesian National Quality Award Promotion Media SNI Award Through Six Thinking Hatss, Value Focus Thinking, and Analytic Hierarchy Process Methods - Silviana, Celly; Novan, Santi; PriHatsiningrum, Tintin (Journal of Economics and Business UBS, 2023)
This study uses the Six Thinking Hats Method, Value Focus Thinking, and Analytic Hierarchy Process, which aims to determine the most appropriate promotional media and can provide maximum benefits in achieving the target interest of SNI Award participants. The study results show tHats five criteria influence the selection of promotional media for the SNI Award: audience reach, ease of use, content, cost, and budget, as well as the reputation of a promotional media. While the best alternative promotional media is Offline socialization in collaboration with local governments, LPK, and Associations, with a weight value of 0.208, offline socialization activities play an essential role in creating deeper bonds and being able to convey the completeness of information on the benefits of the SNI Award which is more communicative. BSN can design a massive series of offline socialization through several events such as seminars, training, and others to significantly capture the interest of new participants and maintain the loyalty of old participants. BSN can also carry out institutional cooperation by signing MOUs with associations and other government agencies. BSN can also make a well-known figure to become an icon of the SNI Award, where the figure contributes to standardization and is known to a broad audience, primarily by SNI application organizations.